House of Nan Onam Tribe Kuantan Taluk State Kuantan Singingi Regency (2003-2014) - Aliyah, Annisa Nur; Bunari, Bunari; Ahmal, Ahmal (Jurnal Pendidikan Amartha, 2024)
This article is entitled "House of Godang, Nan Onam Tribe, Kenegerian Taluk Kuantan, Kuantan Singingi Regency (2003-2014)". The purpose of this research is to find out the history of the godang house of the Nan Onam tribe in Kenegerian Taluk Kuantan, to find out the function of the godang house of the Nan Onam tribe for the people of Kenegerian Taluk Kuantan, and what efforts can be made to maintain traditional activities at the godang house of the Nan Onam tribe in Kenegerian Taluk Kuantan. This research uses a historical approach with data collection techniques through interviews, observations and documents. This research was carried out in Keegrian Taluk Kuantan, Kuantan Singingi Regency, Riau. The data collection process starts from the heuristic stage as the process of finding or collecting historical sources, the second stage, namely verification, is the process of finding the truth from existing historical sources, the third stage, interpretation, namely the activity of interpreting the facts and data that have been obtained, then the final stage, namely historiography. is a way of writing, presenting, or reporting the results of historical research that has been carried out. The results of this research show that the Nan Onam tribe godang house was established in 2003 which was directly authorized by the Regent of Kuantan Singingi Regency, namely Mr. Asrul Ja'far, during the halal bi halal event. In general, the function of building this godang house is to make it easier for children, grandchildren, nephews and nieces to gather in one place to meet each other. The way to maintain the traditions of the Nan Onam tribe's godang house is to provide guidance to children and grandchildren regarding the customs, hold competitions every year, take part in every traditional activity carried out in the Nan Onam tribe's godang house, and not be influenced by foreign cultures due to technological improvements towards modern.